S4_6 Fallout: Put Another Quarter In The Nuke-Box - Duggan, Matt Jackson; Best, Joel Thomas; Croxford, Saul Marcus Benedict (Physics Special Topics, 2017)
In Fallout 4, Mini Nukes can be slung at enemies. We found a nuke to have 2.99 times the explosive energy of a standard issue US Military grenade, and thus determined the mass of Plutonium-239 require to achieve this energy to be 1.06×10−8 kg.